2022
DOI: 10.1186/s12864-022-08720-4
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Sequencing based analysis of bovine endometrium during the maternal recognition of pregnancy

Abstract: Background Maternal recognition is the crucial step for establishing pregnancy in cattle. This study aims to identify endometrial genes and biological pathways involved in the maternal recognition of pregnancy. Caruncular endometrial tissues were collected from Day 15–17 of gestation (pregnant), non-pregnant (absence of conceptus), and cyclic (non-bred) heifers. Results Total RNAs were isolated from the caruncular endometrial tissues of pregnant, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 55 publications
1
8
0
Order By: Relevance
“…COL6A6 was upregulated at all time points, displaying the largest log 2 fold-change at Day 7 post-oestrus (luteal phase) (+9.05). Collagens are diverse and are involved in organizing the extracellular matrix in the endometrium of pregnant bovines, as well as participating in signalling and adhesion [ 46 ]. Collagen VI forms a subepithelial and pericellular fibril sheet in both superficial and deep bovine endometrium, linking cells to the collagen fibril network and localizing around capillaries and smooth muscle cells [ 71 ]: therefore, in this case it could have a function in reorganizing cells, particularly the vasculature of the endometrium during this period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…COL6A6 was upregulated at all time points, displaying the largest log 2 fold-change at Day 7 post-oestrus (luteal phase) (+9.05). Collagens are diverse and are involved in organizing the extracellular matrix in the endometrium of pregnant bovines, as well as participating in signalling and adhesion [ 46 ]. Collagen VI forms a subepithelial and pericellular fibril sheet in both superficial and deep bovine endometrium, linking cells to the collagen fibril network and localizing around capillaries and smooth muscle cells [ 71 ]: therefore, in this case it could have a function in reorganizing cells, particularly the vasculature of the endometrium during this period.…”
Section: Discussionmentioning
confidence: 99%
“…The quality of the individual 29 raw RNA-seq sample library files was assessed with the FastQC software (version 0.11.5) [ 44 ]. Paired-end reads from each individual library were aligned to the Bos taurus reference genome (UMD3.1.1 –GCF_000003055.6; [ 45 , 46 ], from the NCBI RefSeq database [ 47 ], using the STAR aligner software (version 2.5.1b) [ 48 ]. Following this, the aligned SAM files were quality-assessed with FastQC.…”
Section: Methodsmentioning
confidence: 99%
“…Further, we found that the host genes of these DEcircRNAs are also involved in multiple pregnancy-related biological processes, including " biological adhesion “, “reproductive process” and “growth”. Previous studies have found that MRS2 (ssc_circ:chr7:19265492_19273195(+) host gene) is up-regulated in bovine pregnant endometrium and may be involved in the regulation of maternal recognition of pregnancy [ 66 ]. Studies have shown that CDH13(ssc_circ:chr6:5297087_5377909(-) host gene) is up-regulated in the porcine endometrium during implantation and is a gene related to implantation and pregnancy establishment in pigs [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, while MS4A8 was found to be highly expressed selectively in cDC2 (c5, c9) and putative inflammatory cDC2 (c3, left part), it appeared to be absent from putative moDC (c3, right part). The function of MSA48 is poorly characterized, but it was recently found to be highly upregulated in bovine pregnant endometrium (55) and in blood of Salmonella-infected pigs (56).…”
Section: Co-clustering Of Inflammatory Cdc2 Monocyte-derived DC and P...mentioning
confidence: 99%